2021
DOI: 10.18502/ajmb.v13i2.5529
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Silver Nanoparticles on Pyocyanin Production of Pseudomonas aeruginosa Isolated From Clinical Specimens

Abstract: Background: Pseudomonas aeruginosa (P. aeruginosa) is an opportunistic pathogen causing a wide range of human infections. The organism is resistant to a wide range of antibiotics. The purpose of this study was to investigate the effect of AgNPs on pyocyanin pigment production of P. aeruginosa bacteria isolated from clinical specimens. Methods: In this study, 15 clinical isolates of P. aeruginosa were collected from different specimens of hospitalized patients. P. aeruginosa was detected by biochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…Small round to fibrous type cells verified the impact of inhibition (Fig 9 ). A similar study of the Hep-G2 cell viability was reported previously [61]. The cytotoxicity of AgNPs is a direct result of oxidative stress induced by Ag ion release from AgNPs.…”
Section: Cytotoxic Activitiessupporting
confidence: 82%
“…Small round to fibrous type cells verified the impact of inhibition (Fig 9 ). A similar study of the Hep-G2 cell viability was reported previously [61]. The cytotoxicity of AgNPs is a direct result of oxidative stress induced by Ag ion release from AgNPs.…”
Section: Cytotoxic Activitiessupporting
confidence: 82%
“…Pseudomonas aeruginosa is an opportunistic pathogen belonging to the ESKAPE group, often associated with nosocomial infections and complications in cystic fibrosis patients (Hall et al 2016;Grygorcewicz et al 2020). Therefore, many researchers focus on eliminating P. aeruginosa employing different nanomaterials, mainly metal oxides (Lee et al 2014;Zanni et al 2017;Saleh et al 2019;El-Deeb et al 2020;Ali et al 2020;Najafi et al 2021) However, it was reported that Pseudomonas spp. biofilm formation or cell respiration can be stimulated by nanomaterials, such as silver nanoparticles, zinc oxide, and hybrid nanomaterial consisting of silica nanotubes modified with titanium dioxide (Yang and Alvarez 2015;Augustyniak et al 2020;Ouyang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…After incubation, the first well in which no growth was observed was considered as MIC. From this dilution and higher dilutions, 10 μL were taken on nutrient agar culture medium, the dilution in which no growth was observed was considered as MBC [34].…”
Section: Methodsmentioning
confidence: 99%